Hepatitis B virus remains the leading cause of cirrhosis of liver in Bangladesh (Bangladesh Medical Journal, 2017)
Cirrhosis is a serious and irreversible disease. It is a consequence of chronic liver disease characterized by replacement of liver tissue by fibrotic scar tissue as well as regenerative nodules, leading to progressive loss of liver function. Present study was conducted to evaluate the aetiological factors of liver cirrhosis. This was a retrospective cross-sectional study. Patients attending Hepatology Green Unit, Bangabandhu Sheikh Mujib Medical University, Dhaka in 2014 with cirrhosis were included. Total 770 patients were studied, 525(68.18%) males and 245(31.82 %) females. Majority of patients, 379(49.22%) had HBV infection, 162(21.04%) had NASH, 113(14.68%) had HCV infection, 31(4.02%) had alcohol abuse, 28(3.64%) had Wilsons disease , 23(2.98%) had autoimmune hepatitis and no etiological factors (cryptogenic) were recorded in 34 (4.42%) patients. HBV infection was the major risk factor for cirrhosis in our patients.Bangladesh Med J. 2016 Sep; 45 (3): 164-166